2014
DOI: 10.2217/imt.14.37
|View full text |Cite
|
Sign up to set email alerts
|

Peptides and Peptidomimetics as Immunomodulators

Abstract: Peptides and peptidomimetics can function as immunomodulating agents by either blocking the immune response or stimulating the immune response to generate tolerance. Knowledge of B- or T-cell epitopes along with conformational constraints is important in the design of peptide-based immunomodulating agents. Work on the conformational aspects of peptides, synthesis and modified amino acid side chains have contributed to the development of a new generation of therapeutic agents for autoimmune diseases and cancer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 138 publications
(141 reference statements)
0
52
0
1
Order By: Relevance
“…There are many authoritative reviews of peptides as vaccines and peptidomimetics as immunomodulators. [58][59][60][61] Other advantages of peptide therapeutics include: low cost, higher specificity and potency; due to their superior compatibility with targeted proteins, ability to penetrate the cell membrane, lack of immunogenicity and improved safety profiles.…”
Section: Peptide Mimics As Safe Therapeuticsmentioning
confidence: 99%
“…There are many authoritative reviews of peptides as vaccines and peptidomimetics as immunomodulators. [58][59][60][61] Other advantages of peptide therapeutics include: low cost, higher specificity and potency; due to their superior compatibility with targeted proteins, ability to penetrate the cell membrane, lack of immunogenicity and improved safety profiles.…”
Section: Peptide Mimics As Safe Therapeuticsmentioning
confidence: 99%
“…Several types of naturally occurring or synthetic oligopeptides and peptides have been reported to show immunomodulatory and anti-inflammatory activities [1][2][3][4] . Clinically used immunosuppressive drug cyclosporine has a cyclic peptide structure 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Immunomodulatory and anti-inflammatory activities of several types of naturally occurring or synthetic oligopeptides and peptides have been reported [1][2][3][4] . We have also found that certain types of peptide antibiotics suppress proliferation and several cytokine productions in mitogen-activated human peripheral blood mononuclear cells (PBMCs) 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…). Immunomodulation is necessary to control the consequences of a deregulated immune system, and bioactive peptides represent a potential alternative for disease management, as they have low toxicity and do not tend to accumulate in body tissues (Gokhale and Satyanarayanajois ; Agyei et al . ).…”
Section: Immunomodulatory Properties Of Milk‐derived Peptidesmentioning
confidence: 99%